CFD Modeling of Narasena Bengawan UV Team Quickster UAV Wings with Addition of Vortex Generator to Aerodynamic Performance - Mohammad Fahmi Luthfi; Dominicus Danardono; Eko Prasetya Budiana; Yudi Kurniawan (Mekanika: Majalah Ilmiah Mekanika, 2021)
This research is based on obtaining the best possible aerodynamic performance for the Quickster Narasena Bengawan UV Team Unmanned Aerial Vehicle (UAV) aircraft wing design. One factor that significantly affects the flying version of a UAV is the wing. The Quickster Narasena UAV aircraft wing uses an MH33 airfoil because MH33 is specifically for high-speed UAV aircraft. This research will compare the performance of a branch without a vortex generator with addition with a vortex generator. This study will also discuss variations in the positioning of the vortex generator on the wing of the Quickster Narasena UAV. The method used in this research is the Computational Fluid Dynamics (CFD) method. The simulation process will use the ANSYS Fluent 19.0 application with the K-Omega Shear Stress Transform (SST) method with the Reynolds-Averaged-Navier-Stokes (RANS) equation as the basis. This study aims to obtain the results of the coefficient of drag, lift, and the contour of the turbulence that will occur. The simulation results that have been done are the geometry of the wing with the addition of a vortex generator can reduce the drag coefficient and can increase the lift coefficient.